(untitled) (Psychology Travelogs, 2024)
The article conducts a theoretical study of the concepts of professional identity of future counseling psychologists and supervision. It has been established that professional identity is one of the most important components of a person’s “I” concept, acts as an indicator of his involvement in the professional community and a condition for the quality of the activities performed. Conscious professional self-identification is a decisive factor in success or failure in work. In the article, the professional identity of a psychologist is understood as a personal new formation, which has its structure in the form of three main components: cognitive-semantic, emotional-volitional and behavioral. It is presented that professional identity is one of three criteria that reveal the content of the concept of professional development of an individual. Professional development is a certain form of activity, with the help of which one can testify to the level of development of a professional and his professionalization. The purpose of the article is a theoretical and empirical study of supervision as an important part of assistance in the professional development and formation of the professional identity of a consulting psychologist, as well as an empirical determination of the formation of a psychologist’s professional identity and the ability to obtain supervision. Using the author’s methodology to determine the professional identity of a psychologist, a general indicator was studied and the formation of various components of identity was determined: emotional-volitional, behavioral and cognitive-semantic. A comparison of samples of psychologists according to the average values of the components of professional identity showed a significant difference among those who use supervision for professional development. The results obtained made it possible to assert that supervision is important not only for a separate component of professional identity, but allows one to intensify the development of all elements of identity.